Design of TTL Based Routing Algorithm on UTAR Network on Chip Communication Architecture - Wahyudi Khusnandar; Fransiscus Ati Halim; Felix Lokananta (Universitas Multimedia Nusantara, 2018)
XY adaptive routing protocol is a routing protocol used on UTAR NoC communication architecture. This routing algorithm adapts shrotest-path first algorithm, which will forward will not be able to work optimally if the closest route no longer have enough bandwidth to continue the packet. Packet will be stored inside the router and forwarded to the nearest router when closest route has enough bandwidth. This paper suggest TTL based routing algorithm to resolve this issue. TTL based routing algorithm adapts XY adaptive routing protocol by adding several parameters on RTL UTAR NoC and additional bit in each packet sent by router. This additional bit and parameter will be used by TTL based algorithm as additional factors in choosing alternative routes inside the communication architecture. Use of TTL on TTL based routing different from use of TTL on communication network. Packets that carry TTL value that equal to Maximum TTL will be route using XY adaptive routing protocol. TTL based routing algorithm has shown better performance compared to XY adaptive routing on some of the experiment done using MSCL NoC Traffic Pattern Suite. This research also proves that TTL based routing algorithm cannot work optimally on small-scaled architecture. Keywords—UTAR NoC; XY Adaptive Routing Protocol; MSCL Traffic Pattern Suite; RTL; TTL (keywords)